Analisis Biaya Transaksi dalam Usahatani Padi di Desa Wilayut Kecamatan Sukodono : Informasi dan Negosiasi - Kurniasari, Desita Syafa; Nuriah Yuliati; Mirza Andrian Syah (Fakultas Pertanian - UMJ, 2025)
Rice farming plays an important role in supporting food security and the farmers' economy. However, the amount of transaction costs that arise during farming and marketing activities is an obstacle that can reduce farmers' income. This study aims to identify the form and type of transaction costs and analyze the effect of marketing channels on farmers' income through transaction costs as an intervening variable. This study uses a quantitative approach with sampling techniques using probability sampling using proportional random sampling and obtained 61 rice farmers in Wilayut Village, Sukodono District, Sidoarjo Regency as respondents. The results showed that marketing channels had a positive and significant effect on transaction costs, while transaction costs had a negative and significant effect on farmers' income. Transaction costs incurred by farmers include input procurement, labor sourcing, farmer group meetings, and selling costs such as transportation, information, and negotiation. The average total transaction costs incurred reached IDR 296,676/ha/season. These results indicate that selecting efficient marketing channels can reduce the burden of transaction costs and contribute to increasing farm income.